A Search for Asymmetric Kinematic Components in Circumstellar Envelopes Using OH Main Line Masers - Jia-Yong Xie; Jun-ichi Nakashima; Yong Zhang (The Astrophysical Journal)
Circumstellar OH maser lines are useful for studying the dynamics of the circumstellar envelope (CSE) around evolved stars. This study aims to identify CSEs around cold stars, which exhibit deviations from the spherical expansion, by comparing the velocity ranges of the OH main lines (1665/1667 MHz) with those of the satellite line (1612 MHz), using a database of circumstellar OH maser sources. We performed this comparison for 377 circumstellar OH maser sources. In addition, using infrared two-color diagrams, we examined the evolutionary stages and infrared properties of objects showing velocity excess (velocity excess means the detection of the main lines outside the velocity range of the satellite line). A periodicity analysis of the Wide-field Infrared Survey Explorer (WISE) light curves was also carried out. As a result of the velocity range comparison, eight circumstellar OH maser sources were found to exhibit velocity excess. The infrared colors of these objects match those of postasymptotic giant branch (AGB) stars. Periodic variations were observed in the WISE light curves of five of these eight objects. The results suggest that examining the velocity excess of the main lines relative to the satellite line is scientifically significant because mainline masers probe the CSE dynamics over a broader range of evolutionary stages compared to the 22.235 GHz H _2 O maser line. Additionally, during the post-AGB phase, the emission regions of the mainline and 22.235 GHz H _2 O masers may overlap in a CSE, whereas they originate from different regions during the AGB phase.